Too much to ask : Black women in the era of integration - Higginbotham, Elizabeth (Gender & American culture., 2001)
In the 1960s, increasing numbers of African American students entered predominantly white colleges and universities in northern and western USA. This work focuses on the women of this pioneering generation, examining their educational strategies and experiences.